The Raiding of Local 480: A Historic Cold War Struggle for Union Supremacy in a Small Canadian City - Verzuh, Ron (Labour / Le Travail, 2018)
The arduous struggle to form Local 480 of the International Union of Mine, Mill and Smelter Workers (Mine-Mill) at Trail, British Columbia, began in 1938. By 1944 it had been certified as the legal bargaining agent for the 5,000 workers at the Consolidated Mining and Smelting Company of Canada (cm's). But being certified did not spell the end of its problems. Even as World War II was winding down, local and continental anti-Communists attacked the Communist leaders who had founded the local. Among the most determined of the attackers was the United Steelworkers of America (uswa). As the Cold War began, Local 480 was girding for a two-year battle to protect itself from the raiding uswa. Sanctioned by the Congress of Industrial Organizations (cio) to subsume Mine-Mill across North America, the Steelworkers employed an aggressive anti-Communist strategy. In early 1950, when this account begins, Local 480 was in a fight for its life.